EFFECTIVENESS OF ONLINE PUBLIC ASPIRATIONS AND COMPLAINTS SERVICES AT THE COMMUNICATION, INFORMATICS AND STATISTICS SERVICE OF BANJARMASIN CITY - Normajatun, Normajatun; M Sayuti Enggok; Fika Fibriyanita; Riska Aulia Nur; Nasya Sahidia (International Journal of Social Science, 2025)
This study aims to describe the effectiveness of online community aspiration and complaint services at the Communication, Information and Statistics Office of Banjarmasin City. The research method was carried out with a qualitative approach. Data was obtained by conducting interviews and supported by documentation review. Data analysis is descriptive qualitative. The results showed that online community aspiration and complaint services were effective as measured by indicators: goal achievement, integration and adaptation were effective but not optimal